PELUANG PENELITIAN PENDIDIKAN ISLAM DAN KECERDASAN BUATAN DI ERA DIGITAL - Tita Hasanah; Zainal Arifin; Lina Najwatur Rusydi; Supiyandi (JURNAL KAJIAN ISLAM MODERN, 2026)
This study aims to map the trends and characteristics of scientific publications related to Islamic education in the context of digital technology and artificial intelligence. The approach used is a literature analysis based on Scopus-indexed publications through a qualitative descriptive method. Data were collected using a search string combining the terms Islamic education with digital technology, ICT, and artificial intelligence, conducted on November 19, 2025. A total of 214 documents published during the period 2009–2025 were analyzed based on annual publication trends, geographic distribution of authors, subject areas, and document types. The results show a very significant increase in publications in the last three years, indicating a strengthening academic attention to the integration of technology in Islamic education. Indonesia and Malaysia are the main contributors to publications, indicating Southeast Asia's strategic role as a center for the development of technology-based Islamic pedagogy. In terms of subject areas, studies are dominated by social sciences and humanities, while contributions from computer science are relatively limited, indicating the lack of technical research related to the development of artificial intelligence models based on Islamic values. The dominance of journal articles also indicates a gap between theoretical development and practical implementation in educational institutions. These findings confirm that opportunities for research on Islamic education in the digital and artificial intelligence era are still very open, both in the conceptual, pedagogical, ethical, and technical realms, so that a more applicable research agenda based on Islamic values ​​is needed to ensure the use of technology is in line with the goals of Islamic education.